Análisis de Nivel de Reparación (LORA) en el marco del soporte logístico integrado de COTECMAR mediante interfaz gráfica (2024)
This degree work focuses on the development of an innovative program designed to implement Level of Repair Analysis (LORA) within the framework of integrated logistics support. Developed using Python, a powerful and versatile programming language, the platform facilitates decision-making in terms of maintenance and repair of equipment, integrating cost analysis. The design and functionality of the platform are guided by several key military standards, including MIL-HDBK-1390, MIL-HDBK-217F, MIL-STD- 1388, MIL-STD-1390D, MIL-STD-2173, and MIL-STD-1629, ensuring compliance with rigorous maintenance and reliability criteria. The LORA methodology, applied through an intuitive interface and advanced analytical tools, allows users to evaluate different repair and maintenance options efficiently and effectively. This project combines theory and technology to provide customized solutions, significantly improving logistics management in diverse operating environments. The program represents a breakthrough in the application of data analysis and process optimization in the field of logistics, with significant potential to reduce costs and improve the operational availability of equipment.